Calcium hydroxide: A boon in complete healing of horizontal apical one-third root fracture - Pushpendra K Verma; Ruchi Srivastava (Wolters Kluwer Medknow Publications, 2012)
Introduction: A variety of traumatic conditions can cause root fractures. The root fractures are more likely to occur in fully erupted permanent maxillary central incisors with a completely formed root followed by the maxillary lateral and the mandibular incisors. They involve the dental pulp, supporting tissues, and the mineralized structures of a tooth. Diagnosis of the horizontal root fractures is mainly reached by the information obtained in clinical and radiographic examinations. Case Report: This case report describes the management of the horizontal apical one-third root-fractured tooth without surgical removal of the apical fragment, by long-term calcium hydroxide dressing with good signs of healing of fracture at 3 months followed by conventional root canal treatment with the follow-up examination for 1 year after the completion of treatment. Discussion: Calcium hydroxide has showed a miracle in successful healing of apical one-third root fracture.